2010
DOI: 10.1063/1.3452367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GeO desorption behavior in the metal/GeO2/Ge structure and its improvement of the electrical characteristics

Abstract: The relation between germanium monoxide (GeO) desorption and either improvement or deterioration in electrical characteristics of metalGeO(2)Ge capacitors fabricated by thermal oxidation has been investigated. In the metalGeO(2)Ge stack, two processes of GeO desorption at different sites and at different temperatures were observed by thermal desorption spectroscopy measurements. The electrical characteristics of as-oxidized metalGeO(2)Ge capacitors shows a large flat-band voltage shift and minority carrier gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…Meanwhile, another peak located at higher binding energy was deconvoluted into five contributions: four are oxide of Ge, i.e., sub-oxides Ge2O (Ge 1+ ), GeO (Ge 2+ ), Ge2O3 (Ge 3+ ), and native oxide GeO2 (Ge 4+ ); another bonding state component is Ge*, i.e., germanate (Hf(Ti)-Ge-O) between the Ge 3+ and Ge 4+ components [29] . Among of them, Ge 2+ , Ge 4+ and germanate will lead to poor interfacial properties compared with Ge 1+ and Ge 3+ , since the three formers are thermally more unstable than the two latter [30] . It can be seen distinctly that intensities of native oxide GeO2 and germanate are reduced after being pretreated with TMA or Al2O3.…”
Section: Interface Bonding State Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…Meanwhile, another peak located at higher binding energy was deconvoluted into five contributions: four are oxide of Ge, i.e., sub-oxides Ge2O (Ge 1+ ), GeO (Ge 2+ ), Ge2O3 (Ge 3+ ), and native oxide GeO2 (Ge 4+ ); another bonding state component is Ge*, i.e., germanate (Hf(Ti)-Ge-O) between the Ge 3+ and Ge 4+ components [29] . Among of them, Ge 2+ , Ge 4+ and germanate will lead to poor interfacial properties compared with Ge 1+ and Ge 3+ , since the three formers are thermally more unstable than the two latter [30] . It can be seen distinctly that intensities of native oxide GeO2 and germanate are reduced after being pretreated with TMA or Al2O3.…”
Section: Interface Bonding State Characteristicsmentioning
confidence: 98%
“…Although these surface pretreatment technologies could improve the electrical characteristics of Ge MOS, introduction of a passivation layer with low dielectric constant does not meet the requirements of the aggressive device scale [7] . Moreover, Ge oxide easily grows on Ge surface exposed to air for a very short time, even after chemical pretreatment with HF or HCl [11] .In recent years, it has been demonstrated that the native oxide on Ш-V semiconductors (GaAs, InSb, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 As discussed above with Fig. 10(c), infiltrated water molecules cause hydroxylation to generate hole-trap states in the suboxide layer of GeO 2 films.…”
Section: B Ap-xps Experimentsmentioning
confidence: 99%
“…One could extrapolate that the GeO desorption effect not only causes loss of GeO 2 , but also causes loss of the underlying Ge substrate. Recently Oniki et al did a Ge/GeO 2 desorption study with thermal desorption spectroscopy [39]. The authors found that oxide desorption occurs above 400…”
Section: Gate Dielectricsmentioning
confidence: 99%